Alterità e identità nella teoria letteraria: il problema della mimesis - Gilodi, Roberto (Filosofia, 2015)
The concept of verisimilitude is central to Aristotle’s Poetics. It entails the representation of the universal in the narration of possible events. During the Renaissance, and particularly in Torquato Tasso’s theory of epic poetry, the verisimile was to be allied with the meraviglioso. Lastly, in the modern novel verisimilitude is that which is based on natural truth. In these three concepts of verisimilitude we note the equivalence of mimesis and poiesis, and in this light, despite the obvious differences, the essential continuity, from this point of view, between the classical and realistic poetics.